Comparison of the Single and Double Flowered Portulaca Varieties in Bee Attraction - Wongpiyasatid, Arunee; Hormchan, Praparat (Agriculture and Natural Resources, 2001)
New portulaca mutants of 2 single, Chompoo Praparat and Pattik, and 1 double, Som Arunee, flowered types obtained through gamma irradiation were tested for bee attraction against the original varieties of Double Pink and Double Orange. The counting of three kinds of bees, Apis mellifera, Apis cerana indica and Trogina spp, visiting each variety at a 40-minute period with 4 replicates, in the planting plot at the Department of Applied Radiation and Isotopes, Kasetsart University, were undertaken from November 2000 through February 2001. It was found that the single mutants with easy access to pollens attracted significantly greater amount of A. cerana indica than the double varieties which tended to hide stamens under their multi-petals. The other 2 species of bee were of too little in number to be statistically analyzed. The 5-petal mutants were also noticed to have more stamens than the multi-petal flowers did, another possibly attractive cause to bee besides the flower type.